Postrzeganie dziecka przez wychowawcę w żłobku - Lucyna Telka (Problemy Wczesnej Edukacji)
The article contains a report of research on the experience of educators of young children in creche. The strategy of the constructivist theory established by K. Charmaz allowed, during the coding of data, to ask the question of what is the representation of the child in the narratives of the educators in a situation of play and organized activity. The concept of developmental accompaniment and the child’s initiative in the activity undertaken, pointed out by the narrators, became the starting point for the emergence of elements of a theory grounded in the data concerning the perception of the child by the educator in the creche, namely the concept of the causative child and the of efficient child.